Validity of lactate thresholds in inline speed skating - Hecksteden, A.; Heinze, T.; Faude, O.; Kindermann, W.; Meyer, T. (The Journal of Strength and Conditioning Research, 2015)
Lactate thresholds are commonly used as estimates of the highest workload where lactate production and elimination are in equilibrium (maximum lactate steady state [MLSS]). However, because of the high static load on propulsive muscles, lactate kinetics in inline speed skating may differ significantly from other endurance exercise modes. Therefore, the discipline-specific validity of lactate thresholds has to be verified. Sixteen competitive inline-speed skaters (age: 30 ± 10 years; training per week: 10 ± 4 hours) completed an exhaustive stepwise incremental exercise test (start 24 km/h, step duration 3 minutes, increment 2 km/h) to determine individual anaerobic threshold (IAT) and the workload corresponding to a blood lactate concentration of 4 mmol/L (LT4) and 2-5 continuous load tests of (up to) 30 minutes to determine MLSS. The IAT and LT4 correlated significantly with MLSS, and the mean differences were almost negligible (MLSS 29.5 ± 2.5 km/h; IAT 29.2 ± 2.0 km/h; LT4 29.6 ± 2.3 km/h; p > 0.1 for all differences). However, the variability of differences was considerable resulting in 95% limits of agreement in the upper range of values known from other endurance disciplines (2.6 km/h [8.8%] for IAT and 3.1 km/h [10.3%] for LT4). Consequently, IAT and LT4 may be considered as valid estimates of the MLSS in inline speed skating, but verification by means of a constant load test should be considered in cases of doubt or when optimal accuracy is needed (e.g., in elite athletes or scientific studies).